THE EU AND ENVIRONMENTAL PROTECTION: CYPRUS AT THE CROSSROADS OF EUROPE - Emine Eminel Sülün; Zehra Azizbeyli (Ankara Avrupa Çalışmaları Dergisi)
Environmental challenges are on the increase every day and the protection of European ecosystems is becoming more critical for the European Union (EU). Through the European environment policy framework, various instruments have been introduced but the Turkish Republic of Northern Cyprus (TRNC) is an exceptional case where the acquis communautaire is suspended until a political settlement is reached. This paper examines together the EU’s ability in providing environmental security as an element of environmental protection within its borders and problematizes the EU engagement in the TRNC and environmental protection on the island. The EU’s abilities and its capacity in the protection of the environment in Cyprus can be enhanced by engaging more with the Turkish Cypriot authorities on the issues of environmental protection.